Pharmaconutraceutical Chondroguard®TRIO – chondroprotector with immunomodulatory activity - O. A. Shavlovskaya; Yu. D. Yukhnovskaya; I. D. Romanov; I. A. Bokova (Неврология, нейропсихиатрия, психосоматика)
Understanding the major pathological pathways and the key molecules involved in the pathogenesis of inflammatory processes in joints, particularly in osteoarthritis (OA), is crucial for drug and pharmaconutraceuticals development. OA is a degenerative joint disease that predominantly affects articular cartilage. Destruction of hyaline cartilage and restructuring of subchondral bone are accompanied by synovial inflammation in the joint, including the facet joint of the spine, manifested by pain in the joint, low back pain (LBP), and limitation of functional activity. The article discusses the relationship between immune and inflammatory mechanisms in OA of any location, including the joints of the spine. One of the mechanisms for the formation of a “vicious circle of inflammation” during the activation of discoidin receptors by endogenous type II collagen is discussed, leading to the induction of the synthesis of pro-inflammatory mediators: tumor necrosis factor α(TNFα), metalloproteinases (MMPs) 1 and 13, interleukins (IL) 1 and 6. Inflammation, in turn, leads to a decrease in the synthesis and destruction of endogenous type II collagen and, subsequently, to cartilage destruction. Cartilage fragments entering the joint space of the intercellular matrix enhance the synthesis of TNFα, IL, and MMP and exacerbate the inflammatory process. Oral ingestion of exogenous undenatured type II collagen(NK-II) helps, first, to inactivate the binding of fragments of destroyed endogenous type II collagen to discoidin receptors and to break the "vicious circle of inflammation"; secondly, through the mechanism of oral/intestinal tolerance via the lymphoid system in Peyer's patches of the small intestine, leads to the activation of immune cells (T-lymphocytes) and initiation of the immune response – the synthesis of anti-inflammatory mediators (transforming growth factor β, IL4 and IL10). The new pharmaconutraceutical Chondroguard®TRIO, which contains chondroprotectors (chondroitin sulfate and glucosamine sulfate) as well as NK-II, will make it possible to influence the key sites of the pathological process in OA.